The role of "Social" in the TSST: social support and social motives partly moderate psychobiological stress responses in addition to biological sex - Schüler, Julia; Zimanyi, Zsuzsanna; Radtke, Vanessa; Stoffel, Martin; Ditzen, Beate (Psychoneuroendocrinology, 2025)
Prior research has highlighted sex differences in psychobiological stress responses during the Trier Social Stress Test (TSST). This study expands on these findings by exploring how social motives (affiliation and power motives) and social support, as direct predictors and in interaction with biological sex, influence stress responses and reproductive hormones. A sample of 204 participants (108 women, 96 men) underwent the TSST, with social support being manipulated. The biological and psychological responses followed patterns previously documented in the literature. Linear mixed-effect models indicated that biological sex moderated the trajectories of RMSSD, testosterone, progesterone, and well-being across the TSST phases. Additionally, cortisol responses were more pronounced in men, particularly those with strong power motives. Participants receiving social support exhibited lower estradiol levels during the TSST recovery phase compared to the control group. These findings suggest that the impacts of social stress are shaped by complex interactions between biological and social factors, which could be considered in tailored stress interventions.